A satirical depiction of the policy of European powers during the Bulgarian Crisis (1885–1886) in Krakow journal “Diabeł” - Chrobak, Waldemar (Laughter, humour, satire, 2024)
The Bulgarian crisis (1885–1886) depicted the growth of the particular interests of the European powers and constituted a violation of the rules of the Berlin Congress (1878) regarding the balance of power in the Balkan region. The ambiguous attitude of the powers towards the dynamic events taking place from the revolution in Eastern Rumelia in April 1885 to the short Serbian-Bulgarian war (November 1885) and the conclusion of the Tophanen Peace (April 1886) was widely commented on in the Polish press of that period. This topic was also taken up by “Diabeł”, an illustrated satirical magazine published since 1869 in Krakow. It featured texts and illustrations mocking the cynical policy of European powers towards the nations of the Balkan Peninsula.